Microcalorimetry of macromolecules the physical basis of biological structures - Privalov, Peter L. (Wiley, 2012)
"This is the first textbook on the microcalorimetry of biological molecules. The coverage starts from the basics of thermodynamics (which are unknown for many scientists working in biology), describes evolution of the calorimetric technique, explains how to analyze the calorimetric data, and illustrates these methods with a wide selection of examples. The book provides an essential resource to scientists studying biological molecular structures and the reactions between these structures"--